Connectives and discourse relations - Zufferey, Sandrine 1978-; Degand, Liesbeth 1967- (Cambridge University Press, 2024)
Illustrated with examples from a rich range of languages and genres, this book provides a state-of-the-art introduction to the meanings and functions of connectives, and the discourse relations they communicate. It begins with theoretical chapters that illustrate the many interfaces present in the study of connectives and discourse relations, using diachronic data to illustrate how connectives incorporate such a wide range of functions in synchronic language use. The second half of the book presents the rapidly growing body of studies that have used empirical data to assess theories of connectives and discourse relations, spanning fields as diverse as discourse processing, first and second language acquisition, and cross-linguistic studies. End-of-chapter discussion questions and lists of further readings are included, along with a comprehensive glossary of key terms. This title is part of the Flip it Open Programme and may also be available open access. Check our website Cambridge Core for details
Title from publisher's bibliographic system (viewed on 22 Feb 2024)
Keywords: Grammar, Comparative and general / Connectives; Discourse analysis; Cognitive grammar; Konnexion; Logische Partikel; Kognitive Grammatik